What Is the Evolutionary Fingerprint in Neutrophil Granulocytes? - Dolz, Gaby (2020)
Over the years of evolution, thousands of di erent animal species have evolved. All these species require an immune system to defend themselves against invading pathogens. Nevertheless, the immune systems of di erent species are obviously counteracting against the same pathogen with di erent e ciency. Therefore, the question arises if the process that was leading to the clades of vertebrates in the animal kingdom—namely mammals, birds, amphibians, reptiles, and fish—was also leading to di erent functions of immune cells. One cell type of the innate immune system that is transmigrating as first line of defense in infected tissue and counteracts against pathogens is the neutrophil granulocyte. During the host–pathogen interaction they can undergo phagocytosis, apoptosis, degranulation, and form neutrophil extracellular traps (NETs). In this review, wesummarize a wide spectrum of information about neutrophils in humans and animals, with a focus on vertebrates. Special attention is kept on the development, morphology, composition, and functions of these cells, but also on dysfunctions and options for cell culture or storage.